Remodeling Livelihood Vulnerability Indicators for The Informal Food Microentrepreneurs - Hanilyn A. Hidalgo; Michael Cuesta (SEAS (Sustainable Environment Agricultural Science), 2018)
Abstract The informal sector consists of business enterprises that operate outside legal business frameworks. With the huge contribution of the informal sector in economic development, local authorities regard the sector as partners in local development initiatives. Among the industries in the informal sector, the role of the informal food sector in the food value chain is vital in addressing food security issues in the urban community. However, the absence of social protection in the informal sector makes their livelihood more vulnerable to economic losses. The Livelihood Vulnerability Index (LVI) approach is a practical tool for assessing how vulnerable the sector is and which livelihood component contributes to its vulnerability. Inopportunely, studies on LVI are only centered to farming communities. This paper explores the development of livelihood vulnerability indicators that can be utilized to off-farm enterprises predominantly to the informal food microenterprises. The indicators were sourced from LVI and entrepreneurship studies using the major vulnerability factors such as adaptive capacity, sensitivity, and exposure. The developed livelihood vulnerability indicators quantify the seven livelihood components of the informal food microenterprises such as the demographic profile, social network, livelihood strategies, health security, food security, access to utilities and disaster experience. Keywords: remodeling, livelihood vulnerability index, microentrepreneurs.